2022
DOI: 10.22146/ijbiotech.64021
|View full text |Cite
|
Sign up to set email alerts
|

Increased serial levels of platelet‐derived growth factor using hypoxic mesenchymal stem cell‐conditioned medium to promote closure acceler‐ ation in a full‐thickness wound

Abstract: The healing process of a full‐thickness wound involves a complex cascade of cellular responses to reverse skin integrity formation. These processes require growth factors, particularly platelet‐derived growth factor (PDGF). Conversely, hypoxic mesenchymal stem‐cell‐conditioned medium (HMSC‐CM)‐contained growth factors notably contribute to acceleration of wound healing. This study aims to investigate the role of HMSC‐CM in controlling the serial levels of PDGF associated with accelerated wound closure in full‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…We assume that S-HMSC may increase MMP-1 through TGF-β1, IL-1, and IL-6 which are inhibitors of the MMP-1 enzyme synthesis pathway. Previous studies have demonstrated that increased collagen production by fibroblasts may lead to increased deposition into the ECM regulated by the cytokine TGF-β1 [37], [38], [39]. Interestingly, other previous studies have shown that TGF-β1 not only increases collagen production but also inhibits MMPs in the collagen degradation pathway through MMP-3 and MMP-9 [38], [39].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We assume that S-HMSC may increase MMP-1 through TGF-β1, IL-1, and IL-6 which are inhibitors of the MMP-1 enzyme synthesis pathway. Previous studies have demonstrated that increased collagen production by fibroblasts may lead to increased deposition into the ECM regulated by the cytokine TGF-β1 [37], [38], [39]. Interestingly, other previous studies have shown that TGF-β1 not only increases collagen production but also inhibits MMPs in the collagen degradation pathway through MMP-3 and MMP-9 [38], [39].…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have demonstrated that increased collagen production by fibroblasts may lead to increased deposition into the ECM regulated by the cytokine TGF-β1 [37], [38], [39]. Interestingly, other previous studies have shown that TGF-β1 not only increases collagen production but also inhibits MMPs in the collagen degradation pathway through MMP-3 and MMP-9 [38], [39]. TGF-βs bind to two serine/ threonine kinase receptors consisting of TGF-βRI and TGF-βRII [40].…”
Section: Discussionmentioning
confidence: 99%
“…S-HMSCs 100 uL and 200 uL were dissolved in 200 mg of water-based gel as P1 and P2, respectively. The sample was applied topically to the dorsal skin one a day at day 14 until day 28 after UVB-irradiation [28].…”
Section: Secretome Mesenchymal Stem Cells Gel Preparationmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) have the capacity to self-renew and differentiate into other cell types, thereby facilitating the process of cell regeneration [9], [10], [11], [12], [13]. On the other hand, bovine colostrum has antioxidant properties that can aid in tissue repair [14].…”
Section: Introductionsmentioning
confidence: 99%
“…A previous study reported that MSCs are able to accelerate the liver regeneration process [20]. MSCs will produce several paracrine factors including vascular endothelial growth factor (VEGF), hepatocyte growth factor, insulin growth factor, and interleukin 10 (IL-10) that associated with liver regeneration [11], [12], [21], [22], [23]. In addition, bovine colostrum has a total antioxidant capacity, such as superoxide dismutase, glutathione peroxidase, catalase, Vitamin E, Vitamin C, and β carotene [24].…”
Section: Introductionsmentioning
confidence: 99%